Method for producing surface-modified nanodiamonds
By reacting nanodiamonds with glycidol in an aliphatic alcohol solvent, the method achieves efficient production of surface-modified nanodiamonds with improved solubility and dispersibility, addressing the challenges of existing production methods.
Patent Information
- Application Number
- JP2021542780
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-30
- Filing Date
- 2020-08-19
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2040-08-19
AI Technical Summary
Existing methods for manufacturing surface-modified nanodiamonds face challenges in achieving efficient and scalable production with excellent solubility, dispersibility, and dispersion stability in water or polar organic solvents, particularly due to difficulties in controlling temperature and managing contamination during the surface modification process.
The method involves reacting nanodiamonds or nanodiamonds with functional groups that can react with glycidol, in the presence of a specific solvent such as an aliphatic alcohol with 2 to 4 carbon atoms, to smoothly perform ring-opening addition polymerization, resulting in surface-modified nanodiamonds with polyglycerin chains.
This approach allows for the efficient and safe industrial production of surface-modified nanodiamonds with enhanced solubility, dispersibility, and dispersion stability, facilitating their scalability and application in various engineering fields.
Smart Images

Figure 0007649243000001 
Figure 0007649243000002 
Figure 0007649243000003
Abstract
Description
[Technical field]
[0001] This disclosure relates to a method for producing surface-modified nanodiamonds. The surface-modified nanodiamonds can be used in engineering applications such as polishing agents for CMP (Chemical Mechanical Polishing), dresser materials, corrosion-resistant electrode plating materials for fuel cells, high-hardness surface coating layer forming materials for cutting tools, high heat resistance and high thermal conductivity materials, lubricants, and insulating materials. This application claims priority to Japanese Patent Application No. 2019-158008 filed in Japan on August 30, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] Nanodiamonds have the inherent properties of diamond, as well as the characteristics of small average particle size and large specific surface area. Furthermore, they are relatively inexpensive and easily available.
[0003] Nanodiamonds are produced by the detonation method, the high-temperature high-pressure method, the static high-pressure method, the flux method, and the like. Nanodiamond particles produced by the detonation method are produced by subjecting the soot obtained by detonating an explosive in a sealed state to chemical treatment to purify it, dispersing it in water and pulverizing it with a dispersing machine such as a bead mill or an ultrasonic homogenizer to obtain an aqueous dispersion, and then removing water from it by ultracentrifugation, concentration drying, freeze drying, spray drying, and the like. Nanodiamonds obtained by this method have high solubility and dispersibility in water, but have problems such as the inclusion of other carbonaceous substances such as amorphous carbon and graphite, and difficulty in chemically modifying the surface. On the other hand, the high-temperature high-pressure method is a method in which raw graphite powder is kept at a high pressure of 1 to 10 GPa and a high temperature of 800 to 2000 °C in the presence of metals such as iron and cobalt in a sealed high-pressure vessel, and directly undergoes phase transition to diamond. Nanodiamonds obtained by this method contain little contamination with other carbonaceous materials such as amorphous carbon and graphite, and have a uniform particle size, but they have problems with low solubility, dispersibility, and dispersion stability in water and organic solvents, which is why the development of applications for nanodiamonds has not progressed very far.
[0004] Attempts have been made to chemically modify the surface of nanodiamonds in order to improve their solubility and dispersibility in water and organic solvents (see Patent Documents 1 to 3). However, the solubility, dispersibility, and dispersion stability in water or polar organic solvents have not always been sufficient.
[0005] Patent documents 4 and 5 disclose surface-modified nanodiamonds in which the surface of the nanodiamond is modified with a group containing a polyglycerin chain. In these documents, the surface-modified nanodiamonds are produced by heating nanodiamonds or nanodiamonds having reactive functional groups on the surface with glycidol in the presence of a catalyst. However, in this method, nanodiamonds and glycidol are reacted in the absence of a solvent, so when scaled up, it is difficult to control the temperature and the reaction may run out of control, making it difficult to industrialize. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-238411 A [Patent Document 2] JP 2008-303104 A [Patent Document 3] JP 2008-150250 A [Patent Document 4] JP 2010-248023 A [Patent Document 5] JP 2012-082103 A Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, the object of the present disclosure is to provide a method for industrially, efficiently and safely producing surface-modified nanodiamonds whose surfaces are modified with groups containing polyglycerin chains and which have excellent solubility or dispersibility and dispersion stability in water or polar organic solvents. [Means for solving the problem]
[0008] As a result of intensive research to achieve the above object, the inventors of the present disclosure have found that when nanodiamond or nanodiamond having a functional group on its surface capable of reacting with glycidol is reacted with glycidol in a specific solvent, the reaction proceeds smoothly without runaway, and surface-modified nanodiamonds whose surfaces are modified with groups containing polyglycerin chains can be efficiently produced industrially. The present disclosure has been completed based on these findings.
[0009] That is, in one embodiment of the present disclosure, a nanodiamond or a surface thereof is reacted with a compound represented by the following formula (1) in an aliphatic alcohol solvent having 2 to 4 carbon atoms. -X 1 -H (1) [where, X 1 represents -NH-, -O-, -COO-, -PH(=O)O-, -S-, -SO3-, -SO2- or -SiO-. The surface-modified nanodiamond is modified with a group represented by the following formula (2) by ring-opening addition polymerization of glycidol. -XR (2) [In the formula, X represents a single bond, -NH-, -O-, -COO-, -PH(=O)O-, -S-, -SO3-, -SO2- or -SiO-, and R represents a polyglyceryl group.] The present invention provides a method for producing a surface-modified nanodiamond, which provides a surface-modified nanodiamond modified with a group containing a polyglycerin chain represented by the formula:
[0010] In the above production method, it is preferable to carry out the reaction by successively adding glycidol under heating to a mixture of the aliphatic alcohol solvent having 2 to 4 carbon atoms and the nanodiamond or surface-modified nanodiamond used as a raw material.
[0011] In addition, the nanodiamond or surface-modified nanodiamond used as a raw material is preferably a powder obtained by drying a zeta positive single-digit nanodiamond dispersion.
[0012] Furthermore, the amount of the aliphatic alcohol solvent having 2 to 4 carbon atoms used is preferably 10 to 2000 parts by weight per part by weight of the nanodiamond or surface-modified nanodiamond used as a raw material.
[0013] The amount of glycidol used is preferably 10 to 2000 parts by weight per part by weight of the nanodiamond or surface-modified nanodiamond used as a raw material.
[0014] Furthermore, the temperature during the ring-opening addition polymerization is preferably 40 to 180°C. Effect of the Invention
[0015] According to the present disclosure, nanodiamond or nanodiamond having a functional group on its surface that can react with glycidol is reacted with glycidol in a specific solvent, so that the reaction proceeds smoothly without runaway, and surface-modified nanodiamond whose surface is modified with a group containing a polyglycerin chain can be produced industrially efficiently and safely. Also, it can be scaled up. [Brief description of the drawings]
[0016] [Figure 1] 1 is a GPC measurement chart (RI detector) of the surface-modified nanodiamond obtained in Example 8, the surface of which is modified with a polyglycerin chain-containing group. [Diagram 2] This is a GPC measurement chart (UV254 detector) of the surface-modified nanodiamond obtained in Example 8, the surface of which is modified with a polyglycerin chain-containing group. [Diagram 3] 1 is a GPC measurement chart (RI detector) of a surface-modified nanodiamond obtained in Reference Example 1 (known formulation) whose surface is modified with a polyglycerin chain-containing group. [Figure 4] 1 is a GPC measurement chart (UV254 detector) of a surface-modified nanodiamond obtained in Reference Example 1 (known formulation) whose surface is modified with a polyglycerin chain-containing group. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] In one embodiment of the present disclosure, a method for producing a surface-modified nanodiamond includes subjecting nanodiamond or a surface-modified nanodiamond whose surface has been modified with a group represented by formula (1) to ring-opening addition polymerization with glycidol in an aliphatic alcohol solvent having 2 to 4 carbon atoms to obtain a surface-modified nanodiamond whose surface has been modified with a group containing a polyglycerin chain represented by formula (2). 1 represents -NH-, -O-, -COO-, -PH(=O)O-, -S-, -SO3-, -SO2-, or -SiO-. In addition, in formula (2), X represents a single bond, -NH-, -O-, -COO-, -PH(=O)O-, -S-, -SO3-, -SO2-, or -SiO-, and R represents a polyglyceryl group. Hereinafter, a surface-modified nanodiamond whose surface is modified with a group containing a polyglycerin chain represented by formula (2) may be referred to as "ND-XR". Here, ND represents nanodiamond.
[0018] [Nanodiamonds as raw materials] In one embodiment of the present disclosure, the nanodiamond used as the raw material may be produced by any method such as detonation, high temperature and high pressure, static high pressure, and flux. In the present disclosure, the nanodiamond derived from the diamond produced by the detonation method (particularly, the oxygen-deficient detonation method) is preferred because it can obtain nanodiamond particles with an extremely small average particle size of the primary particles. The detonation method includes the water-cooled detonation method and the air-cooled detonation method due to the difference in the heat removal method. In one embodiment of the present disclosure, the nanodiamond derived from the diamond synthesized by the air-cooled detonation method is preferred because it has a small average primary particle size and a large specific surface area. In one embodiment of the present disclosure, the nanodiamond used as the raw material may be a commercially available product or may be synthesized.
[0019] Nanodiamond particles produced by the detonation method are produced by detonating an explosive in a sealed state, purifying the explosion soot obtained by chemical treatment (e.g., acid treatment, oxidation treatment, hydrogenation treatment, etc.), dispersing the soot in water, pulverizing (disintegrating) it using a dispersing machine such as a bead mill or ultrasonic homogenizer, and removing the water from the resulting aqueous dispersion using ultracentrifugation, concentration drying, freeze drying, spray drying, etc.
[0020] Nanodiamond particles produced by detonation or other methods often have various functional groups on their surfaces, depending on the production process. Examples of the functional groups include -NH2, -OH, -COOH, -PH(=O)OH, -SH, -SO3H, -SO2H, and -SiOH. These functional groups can react with glycidol.
[0021] The particle size D50 (median diameter) of the nanodiamond (ND) used as the raw material is 3 to 200 nm in a preferred embodiment of the present disclosure, 7 to 100 nm in another preferred embodiment, and 10 to 40 nm in yet another preferred embodiment.
[0022] [Surface-modified nanodiamonds as raw materials] In one embodiment of the present disclosure, the surface-modified nanodiamond used as a raw material, the surface of which is modified by a group represented by the formula (1), may be a commercially available product or may be a synthetic product. The surface-modified nanodiamond can be obtained by utilizing a known method or reaction from nanodiamond (ND) and a reactant for introducing a surface-modifying group. When introducing a modifying group into nanodiamond, the reactant corresponding to the modifying group may be directly reacted, but the nanodiamond may be first heated in a hydrogen gas flow, for example, at 400 to 1000°C, reduced to hydrogenated nanodiamond (ND-H) (see JP 2007-238411 A), and then reacted with the reactant corresponding to the modifying group.
[0023] The particle size D50 (median diameter) of nanodiamond (ND) or hydrogenated nanodiamond (ND-H) used as the raw material for producing the surface-modified nanodiamond as the raw material is 3 to 200 nm in a preferred embodiment of the present disclosure, 7 to 100 nm in another preferred embodiment, and 10 to 40 nm in yet another preferred embodiment. By selecting the particle size of the raw material nanodiamond, it is possible to obtain surface-modified nanodiamonds with a particle size suitable for the purpose. Depending on the manufacturing method and manufacturing conditions for producing nanodiamonds from graphite, and depending on the classification operation conditions after production, nanodiamonds with various particle sizes can be obtained, and nanodiamonds with various particle sizes can be obtained from existing manufacturers using various manufacturing methods.
[0024] Among the surface-modified nanodiamonds whose surfaces are modified with groups represented by the above formula (1), X 1 Surface-modified nanodiamonds in which is -NH- can be produced, for example, by introducing an amino group into hydrogenated nanodiamond (ND-H). Introduction of an amino group into hydrogenated nanodiamond (ND-H) can be achieved, for example, by heating ND-H to 300 to 800°C in an ammonia stream. It is also possible to chlorinate ND-H in a chlorine stream before reacting with ammonia, and then react with ammonia (see JP 2007-238411 A).
[0025] Among the surface-modified nanodiamonds whose surfaces are modified with groups represented by the above formula (1), X 1 Surface-modified nanodiamonds in which is -O- can be produced, for example, by introducing a hydroxyl group into hydrogenated nanodiamond (ND-H). Introduction of a hydroxyl group into ND-H can be achieved, for example, by adding benzoyl peroxide to ND-H in acetic acid, heating it to esterify it, and hydrolyzing it with an acid or alkali by a conventional method.
[0026] Among the surface-modified nanodiamonds whose surfaces are modified with groups represented by the above formula (1), X 1The surface-modified nanodiamond in which is -COO- can be obtained, for example, by the following method: dispersing the nanodiamond in a suitable dispersion medium such as methylene chloride, oxidizing and cleaving the unsaturated groups present on the nanodiamond surface with ozone to generate aldehyde groups, and further oxidizing the aldehyde groups with air to generate carboxyl groups.
[0027] Among the surface-modified nanodiamonds whose surfaces are modified with groups represented by the above formula (1), X 1 Surface-modified nanodiamonds with -PH(=O)O- can be obtained by the following method. For example, the surface of hydrogenated nanodiamond (ND-H) dispersed in isopropyl alcohol is irradiated with ultraviolet light (254 nm) to generate radicals, which are then captured by an appropriate phosphorus compound (e.g., phosphorous acid, etc.) to introduce phosphinic acid groups onto the nanodiamond surface.
[0028] Among the surface-modified nanodiamonds whose surfaces are modified with groups represented by the above formula (1), X 1 Surface-modified nanodiamonds with -S- can be produced, for example, by irradiating the surface of hydrogenated nanodiamond (ND-H) with ultraviolet light (254 nm) to generate radicals, capturing the radicals with an appropriate alkyl mercaptan or dialkyl disulfide to introduce alkylthio groups onto the nanodiamond surface, and removing the alkyl groups with an appropriate deprotection reagent to produce ND-SH. For example, nanodiamonds dispersed in isopropanol can be irradiated with 254 nm ultraviolet light while reacting with bis(4-methoxybenzyl) disulfide to introduce 4-methoxybenzylthio groups, and then removing the methoxybenzyl groups with a trimethylsilyl bromide-TFA mixture to produce nanodiamonds with thiol groups on the surface.
[0029] The nanodiamond or surface-modified nanodiamond used as a raw material in the present disclosure may be a solid (powder, etc.) obtained by drying a zeta potential positive nanodiamond dispersion (preferably, a zeta potential positive single-digit nanodiamond dispersion), or a solid (powder, etc.) obtained by drying a zeta potential negative nanodiamond dispersion (preferably, a zeta potential negative single-digit nanodiamond dispersion), but a solid (powder, etc.) obtained by drying a zeta potential positive nanodiamond dispersion (particularly, a zeta potential positive single-digit nanodiamond dispersion) is more preferable in terms of ease of post-treatment after the reaction with glycidol (ring-opening addition polymerization of glycidol). In addition, to the extent that the reaction with glycidol is not impaired, a zeta potential positive nanodiamond dispersion (preferably, a zeta potential positive single-digit nanodiamond dispersion) or a zeta potential negative nanodiamond dispersion (preferably, a zeta potential negative single-digit nanodiamond dispersion) may be used as is, or in a wet state that is not completely dried. In addition, when the term "nanodiamond dispersion" is used, it means both the dispersion of the nanodiamond used as the raw material and the dispersion of the surface-modified nanodiamond used as the raw material. In addition, single-digit nanodiamond refers to nanodiamond particles with a particle size D50 (median diameter) of less than 10 nm.
[0030] The nanodiamond dispersion liquid having a positive ζ potential (i.e., the ζ potential is a positive value) can be produced by, for example, subjecting a crude nanodiamond product produced by a detonation method or the like to an acid treatment step, a solution oxidation treatment step, an alkaline hydrogen peroxide treatment step, an oxygen oxidation step, a hydrogenation treatment step, and a crushing step, as necessary, and performing a classification operation as necessary (see JP 2018-70412 A). In the above-mentioned oxygen oxidation step, when non-diamond carbon such as graphite or amorphous carbon is present on the surface of the nanodiamond and an oxygen oxidation reaction occurs on the non-diamond carbon, carbon dioxide is generated and the non-diamond carbon is removed from the nanodiamond surface. In the above-mentioned oxygen oxidation step, when an oxygen oxidation reaction occurs on the surface of the nanodiamond itself, the nanodiamond surface is oxygen-modified. Specifically, functional groups or partial structures containing oxygen atoms are generated on the nanodiamond surface. Examples of such functional groups or partial structures include carbonyl groups, carboxy groups, lactone structures, and acid anhydride structures. In the above-mentioned hydrogenation process, if a functional group or partial structure containing an oxygen atom, such as a carboxyl group, is present on the nanodiamond surface and a hydrogenation reaction occurs in the functional group, the functional group will either become a hydrogen reductant or be removed from the nanodiamond surface.
[0031] From the viewpoint of stably maintaining the dispersion state of nanodiamond particles (including surface-modified nanodiamond particles), the zeta potential of the nanodiamond dispersion with a positive zeta potential (i.e., the zeta potential is a positive value) is 30 mV or more in a preferred embodiment of the present disclosure, 35 mV or more in another preferred embodiment, and 40 mV or more in a further preferred embodiment. In the present disclosure, the zeta potential of the nanodiamond particles (including surface-modified nanodiamond particles) contained in the nanodiamond dispersion is the value measured at 25°C for the nanodiamond particles in the nanodiamond dispersion with a nanodiamond concentration of 0.2% by mass. When it is necessary to dilute the stock solution of the nanodiamond dispersion to prepare a nanodiamond dispersion with a nanodiamond concentration of 0.2% by mass, ultrapure water is used as the diluting solution.
[0032] The nanodiamond dispersion liquid with a negative ζ potential (i.e., the ζ potential is a negative value) can be produced by, for example, subjecting a nanodiamond crude product produced by a detonation method or the like to an acid treatment step, a solution oxidation treatment step, an alkaline hydrogen peroxide treatment step, or further to an oxygen oxidation step, as necessary, and then subjecting it to a crushing treatment in an alkaline pH-adjusted state, and performing a classification operation as necessary (see JP 2018-70411 A). During the crushing treatment, the ζ potential of the nanodiamond particles after the crushing treatment can be made negative by adjusting the pH to the alkaline side. In addition, in the above process, instead of subjecting it to the crushing treatment in an alkaline pH-adjusted state, if it is subjecting it to the crushing treatment in an acidic pH-adjusted state, the ζ potential of the nanodiamond particles after the crushing treatment can be made positive.
[0033] From the viewpoint of stably maintaining the dispersed state of nanodiamond particles (including surface-modified nanodiamond particles), the zeta potential of a nanodiamond dispersion having a negative zeta potential (i.e., a negative value of the zeta potential) is -30 mV or less in a preferred embodiment of the present disclosure, -35 mV or less in another preferred embodiment, and -40 mV or less in yet another preferred embodiment.
[0034] The nanodiamond dispersion can be dried by removing water by known methods such as ultracentrifugation, concentration drying, freeze drying, spray drying, etc. The solid after drying can be made into powder by, for example, pulverization, classification, etc.
[0035] [Aliphatic alcohol solvents with 2 to 4 carbon atoms] Examples of the aliphatic alcohol having 2 to 4 carbon atoms used as a solvent include aliphatic monohydric alcohols such as ethanol, propanol, isopropyl alcohol, n-butanol, isobutyl alcohol, sec-butyl alcohol, and tert-butyl alcohol; and aliphatic polyhydric alcohols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and glycerin. Among these, aliphatic alcohols having 2 to 3 carbon atoms are preferred. Aliphatic alcohols having 2 to 4 carbon atoms have the characteristics of being extremely low in reactivity with glycidol, having a relatively high boiling point (70°C or higher), and having high solubility of polyglycerin (30°C, 80°C). Therefore, side reactions can be suppressed, the reaction rate can be increased, and the nanodiamonds surface-modified with the groups containing polyglycerin chains produced are less likely to settle.
[0036] [reaction] In the present disclosure, glycidol is subjected to ring-opening addition polymerization of the raw material nanodiamond or surface-modified nanodiamond in the aliphatic alcohol solvent having 2 to 4 carbon atoms to produce a surface-modified nanodiamond modified with a group containing a polyglycerin chain represented by formula (2).
[0037] The reaction (ring-opening addition polymerization) between the nanodiamond or surface-modified nanodiamond as the raw material and glycidol can be carried out by, for example, heating the mixture of the aliphatic alcohol solvent having 2 to 4 carbon atoms and the nanodiamond or surface-modified nanodiamond as the raw material to 40 to 180°C in a preferred embodiment of the present disclosure, 60 to 150°C in another preferred embodiment, and 80 to 125°C in yet another preferred embodiment) and gradually adding glycidol. The reaction is preferably carried out under an inert gas atmosphere. If the reaction temperature is too low, the reaction rate decreases, and conversely, if the reaction temperature is too high, by-products are likely to be generated. A catalyst may be used in the reaction. The catalyst may be added in advance to the mixture of the aliphatic alcohol solvent having 2 to 4 carbon atoms and the nanodiamond or surface-modified nanodiamond as the raw material, or may be added gradually to the mixture when glycidol is gradually added. The time for gradually adding glycidol varies depending on the scale, but in a preferred embodiment of the present disclosure, it is 10 minutes to 24 hours, and in another preferred embodiment, it is 20 minutes to 2 hours. After the completion of the gradually adding glycidol, it is preferable to mature the mixture at the above temperature for a predetermined time. In a preferred embodiment of the present disclosure, the maturation time is 10 minutes to 24 hours, and in another preferred embodiment, it is 20 minutes to 6 hours.
[0038] The catalyst may be either an acid catalyst or a basic catalyst. The acid catalyst is preferably trifluoroboron etherate, acetic acid, phosphoric acid, etc., and the basic catalyst is preferably triethylamine, pyridine, dimethylaminopyridine, triphenylphosphine, etc. The reaction proceeds smoothly even without using a catalyst.
[0039] The amount of the aliphatic alcohol solvent having 2 to 4 carbon atoms used is 10 to 2000 parts by weight in a preferred embodiment of the present disclosure, 15 to 300 parts by weight in another preferred embodiment, and 20 to 200 parts by weight in yet another embodiment, relative to 1 part by weight of the nanodiamond or surface-modified nanodiamond used as a raw material. The amount of the glycidol used is 10 to 2000 parts by weight in a preferred embodiment of the present disclosure, 15 to 300 parts by weight in another preferred embodiment, and 20 to 200 parts by weight in yet another embodiment, relative to 1 part by weight of the nanodiamond or surface-modified nanodiamond used as a raw material.
[0040] The reaction can be stopped by cooling the reaction mixture and adding, for example, water to the reaction system. The product can be purified by known or conventional methods, such as washing with a solvent, centrifugation, membrane filtration, drying, etc. This purification operation can remove the solvent, excess glycidol, and by-products (polyglycerin, etc.). In this way, the surface-modified nanodiamond modified with a group containing a polyglycerin chain represented by the above formula (2) can be obtained as a dispersion or powder.
[0041] According to the method of the present disclosure, for example, it is possible to obtain surface-modified nanodiamonds that are surface-modified with a polyglycerin chain-containing group and have the following physical properties: (i) The ratio of surface modification groups to nanodiamonds (ND) (modification group weight / ND weight) (=modification rate) is 0.2 to 3.0, in a preferred embodiment, 0.4 to 2.4, and in another preferred embodiment, 0.6 to 1.8. This ratio can be determined by TG / DTA measurement. (ii) Particle size D50 (median size) is 20 to 60 nm, and in a preferred embodiment, 30 to 50 nm. The particle size D50 (median size) can be measured by DLS (dynamic light scattering). (iii) It does not cause precipitation or turbidity when mixed with an aqueous solution of sodium nitrate. (iv) In GPC measurement, the peak of the main component is at approximately the same position (retention time) and shape as that of a known formulation (Production Example 1 of Patent Document 5), and no other by-products (impurities) are detected.
[0042] The surface-modified nanodiamonds and their dispersions obtained by the method disclosed herein, which have been surface-modified with polyglycerin chain-containing groups, can be used for the various applications described above, but in particular, since they can maintain a stable dispersion state even in a plating solution, they can be suitably used as a material for forming a plating film (plating material). The plating film formed using this surface-modified nanodiamond has excellent surface gloss, strength, and electrical conductivity.
[0043] Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. Each configuration in each embodiment and their combinations are merely examples, and addition, omission, substitution, and other modifications of the configuration are possible as appropriate within the scope of the present disclosure. In addition, each invention according to this disclosure is not limited by the embodiments or the following examples, but is limited only by the scope of the claims. EXAMPLES
[0044] The present disclosure will be described in more detail below based on examples, but the present disclosure is not limited to these examples.
[0045] Production Example 1 (Production of powder obtained by drying ζ positive single-digit nanodiamond dispersion) [Nanodiamond dispersion liquid] A nanodiamond dispersion was produced through the following production process, purification process, oxygen oxidation process, hydrogenation process, and crushing process.
[0046] In the production process, the explosives were first fitted with electric detonators and placed inside a pressure-resistant detonation vessel, which was then sealed. The vessel was made of iron and had a volume of 15 m. 3The explosive used was a mixture of 0.50 kg of trinitrotoluene (TNT) and cyclotrimethylenetrinitroamine, or hexogen (RDX). The mass ratio of TNT to RDX in the explosive (TNT / RDX) was 50 / 50. Next, an electric detonator was detonated to detonate the explosive in the container. The container and its interior were then allowed to cool for 24 hours at room temperature. After cooling, the nanodiamond crude product (containing the aggregates of nanodiamond particles and soot produced by the detonation method) adhering to the inner wall of the container was scraped off with a spatula, and the nanodiamond crude product was collected.
[0047] Next, the crude nanodiamond product obtained by performing the above-mentioned production process multiple times was subjected to an acid treatment in the purification process. Specifically, 200 g of the crude nanodiamond product was added with 6 L of 10 mass % hydrochloric acid to obtain a slurry, which was then heated for 1 hour under reflux at normal pressure. The heating temperature in this acid treatment was 85 to 100°C. Next, after cooling, the solid matter (including nanodiamond aggregates and soot) was washed with water by decantation. The solid matter was repeatedly washed with water by decantation until the pH of the precipitation liquid reached 2 from the low pH side.
[0048] Next, the solution was oxidized or mixed acid treated in the purification process. Specifically, 6 L of 98% by mass sulfuric acid aqueous solution and 1 L of 69% by mass nitric acid aqueous solution were added to the precipitate (containing nanodiamond aggregates) obtained by decantation after the acid treatment to form a slurry, and the slurry was then heated for 48 hours under reflux at normal pressure. The heating temperature in this oxidation treatment was 140 to 160°C. Next, after cooling, the solids (including nanodiamond aggregates) were washed with water by decantation. The supernatant liquid at the beginning of the washing was colored, and the solids were repeatedly washed with water by decantation until the supernatant liquid became transparent to the naked eye.
[0049] Next, 1L of 10% by mass sodium hydroxide aqueous solution and 1L of 30% by mass hydrogen peroxide aqueous solution were added to the precipitate liquid (containing nanodiamond aggregates) obtained by decantation after the solution oxidation treatment to form a slurry, and the slurry was then subjected to a heat treatment for 1 hour under reflux at normal pressure (alkaline hydrogen peroxide treatment). The heating temperature in this treatment was 50 to 105°C. Next, after cooling, the supernatant was removed by decantation. The remaining fraction was then subjected to a drying treatment to obtain a dry powder. The drying method used was evaporation to dryness using an evaporator.
[0050] Next, an oxygen oxidation process was carried out using a gas atmosphere furnace (product name "Gas atmosphere tube furnace KTF045N1", manufactured by Koyo Thermo Systems Co., Ltd.). Specifically, 4.5 g of the nanodiamond powder obtained as described above was placed in the core tube of the gas atmosphere furnace, and nitrogen gas was continuously passed through the core tube at a flow rate of 1 L / min for 30 minutes, after which the flow gas was switched from nitrogen to a mixed gas of oxygen and nitrogen, and the mixed gas was continuously passed through the core tube at a flow rate of 1 L / min. The oxygen concentration in the mixed gas was 4% by volume. After switching to the mixed gas, the inside of the furnace was heated to a heating setting temperature of 350°C. The heating rate was 10°C / min up to 330°C, which is 20°C lower than the heating setting temperature, and then 1°C / min from 330°C to the heating setting temperature of 350°C. Then, while maintaining the temperature condition in the furnace at 350°C, the nanodiamond powder in the furnace was subjected to oxygen oxidation treatment. The treatment time was 3 hours. In this manner, nanodiamond powder was obtained that had undergone the oxygen oxidation step or oxygen oxidation treatment.
[0051] Next, the hydrogenation process was carried out by continuing to use the gas atmosphere furnace described above. Specifically, after nitrogen gas was continuously passed through the gas atmosphere furnace in which the nanodiamond powder that had been subjected to the oxygen oxidation process was placed at a flow rate of 1 L / min for 30 minutes, the flow gas was switched from nitrogen to a mixed gas of hydrogen and nitrogen, and the mixed gas was continuously passed through the furnace tube at a flow rate of 1 L / min. The hydrogen concentration in the mixed gas was 2% by volume. After switching to the mixed gas, the temperature inside the furnace was raised to a heating setting temperature of 600°C. The heating rate was 10°C / min. Then, while maintaining the temperature condition inside the furnace at 600°C, the nanodiamond powder inside the furnace was subjected to hydrogen oxidation treatment. The treatment time was 5 hours. In this manner, nanodiamond powder that had been subjected to the hydrogen oxidation process or hydrogen oxidation treatment was obtained.
[0052] Next, a crushing process was carried out. Specifically, 0.9 g of the nanodiamond powder that had undergone the above-mentioned hydrogenation process and 29.1 ml of pure water were added to a 50 ml sample bottle and mixed to obtain about 30 ml of slurry. Next, the slurry was subjected to a centrifugation process (10 minutes at a centrifugal force of 20,000×g) and then an ultrasonic treatment. In the ultrasonic treatment, an ultrasonic irradiator (product name "ultrasonic cleaner AS-3", manufactured by AS ONE Co., Ltd.) was used to irradiate the slurry with ultrasonic waves for 2 hours. After this, bead milling was carried out using a bead milling device (product name "parallel four-cylinder sand grinder LSG-4U-2L type", manufactured by IMEX Co., Ltd.). Specifically, 30 ml of the slurry after ultrasonic irradiation and zirconia beads with a diameter of 30 μm were put into a 100 ml mill vessel (manufactured by IMEX Co., Ltd.) and sealed, and the device was driven to carry out bead milling. In this bead milling, the amount of zirconia beads charged is, for example, 33% relative to the volume of the mill container, the rotation speed of the mill container is 2570 rpm, and the milling time is 2 hours.
[0053] Next, the slurry or suspension that had undergone the above-mentioned disintegration process was centrifuged using a centrifuge (classification operation). The centrifugal force in this centrifugation process was 20,000×g, and the centrifugation time was 10 minutes. Next, 10 ml of the supernatant of the nanodiamond-containing solution that had undergone the centrifugation process was collected. In this way, a nanodiamond dispersion liquid in which nanodiamonds were dispersed in pure water was obtained. The solid concentration or nanodiamond concentration of this nanodiamond dispersion liquid was 2.1% by mass, and the pH was 8.07.
[0054] <Particle size D50> The particle size distribution of the nanodiamonds in the nanodiamond dispersion obtained as described above was measured by dynamic light scattering. Specifically, the particle size distribution of the nanodiamonds was measured by dynamic light scattering (non-contact backscattering method) using a Malvern device (product name "Zetasizer Nano ZS"). The nanodiamond dispersion subjected to the measurement had a solids concentration or nanodiamond concentration of 2.1 mass%, and was subjected to ultrasonic irradiation using an ultrasonic cleaner. As a result of the measurement, the particle size D50 (median diameter) of the nanodiamonds was 5.05 nm, and the particle size D90 of the nanodiamonds was 7.54 nm.
[0055] Zeta potential The zeta potential of the nanodiamond particles contained in the nanodiamond dispersion obtained as described above was measured by laser Doppler electrophoresis using a Malvern device (product name "Zetasizer Nano ZS"). The nanodiamond dispersion subjected to the measurement was diluted with ultrapure water so that the solid content concentration or nanodiamond concentration was 0.2 mass%, and then subjected to ultrasonic irradiation using an ultrasonic cleaner. The zeta potential measurement temperature was 25°C. As a result of this measurement, the zeta potential of the nanodiamond dispersion was 41.8mV.
[0056] <Electrical Conductivity Measurement> The electrical conductivity of the nanodiamond dispersion obtained as described above was measured at a temperature of 25°C using an electrical conductivity measuring device (product name "TWIN-COND B-771", manufactured by Horiba, Ltd.). The nanodiamond dispersion used for the measurement had a solids concentration or nanodiamond concentration of 2.1 mass%, and had been subjected to ultrasonic irradiation using an ultrasonic cleaner. As a result of this measurement, the electrical conductivity of the nanodiamond dispersion was 25.2 μS / cm wt%.
[0057] [Nano diamond powder] The nanodiamond dispersion obtained as described above was evaporated to dryness using an evaporator to obtain nanodiamond powder. Vacuum heating IR measurement confirmed that the surface of this nanodiamond powder contained functional groups (-NH2, -OH, -COOH, -PH(=O)OH, -SH, -SO3H, -SO2H, -SiOH, etc.) that could react with glycidol.
[0058] Manufacturing Example 2 (Preparation of powder by drying ζ negative single digit nanodiamond dispersion) [Nanodiamond dispersion liquid] As the nanodiamond crude product, air-cooled detonation nanodiamond soot (manufactured by ALIT, Czech Republic) with a primary particle diameter of nanodiamond of 4-6 nm was used. 220 g of air-cooled detonation nanodiamond soot was weighed, 10.7 L of 10% hydrochloric acid solution was added, and the mixture was heated under reflux for 1 hour (acid treatment). After cooling, the mixture was washed with water by decantation until the pH of the precipitate reached 2.5, and the supernatant was removed. Next, 4725 g of 98% sulfuric acid and 50 g of ultrapure water were added to 1625 g of the precipitate (solid content 125 g) (below 40 ° C). 3050 g of chromic acid aqueous solution (chromic acid 1500 g) was added to this, and the mixture was heated under reflux (internal temperature: 141 ° C) for 5 hours, and then cooled to obtain 9450 g of slurry liquid (oxidation treatment). Thereafter, washing with water was carried out by decantation until the color of the supernatant disappeared, and the supernatant was removed as much as possible to obtain a precipitate.
[0059] 1L of 10% aqueous sodium hydroxide solution was added to the precipitate obtained above, and the mixture was heated under reflux for 1 hour. After cooling, the supernatant was removed by decantation, and then 20% hydrochloric acid was added to adjust the pH to 2.5, and then washing was performed by centrifugal sedimentation. Ultrapure water was added to the final centrifugal precipitate to adjust the solid concentration to 8%, and the pH was adjusted to 10 with sodium hydroxide to obtain a pre-dispersion slurry. The pre-dispersion slurry was dispersed using a bead mill. A wet disperser (product name "Ultra Apex Mill UAM-015", manufactured by Kotobuki Industries Co., Ltd.) was used for dispersion. Zirconia beads with a diameter of 0.03 mm, which are the disintegration media, were filled in the wet disperser to 60% of the crushing container volume, and 300 mL of the pre-dispersion slurry was circulated at a flow rate of 10 L / h, and the peripheral speed of the wet disperser was set to 10 m / s to perform disintegration for 90 minutes. The disintegration liquid was then collected, and coarse particles were removed by classification using centrifugation to obtain an aqueous dispersion of nanodiamonds (particle size distribution D50 = 5.4 nm).
[0060] <Particle size D50> The particle size distribution of the nanodiamonds in the aqueous dispersion of nanodiamonds obtained as described above was measured in the same manner as described above. As a result of the measurement, the particle size D50 (median diameter) of the nanodiamonds was 5.4 nm.
[0061] Zeta potential The zeta potential of the nanodiamond particles contained in the nanodiamond aqueous dispersion obtained as described above was measured by the same method as above. As a result of the measurement, the zeta potential of the nanodiamond aqueous dispersion was -41 mV.
[0062] [Nano diamond powder] The aqueous nanodiamond dispersion obtained as described above was evaporated to dryness using an evaporator to obtain nanodiamond powder. The powder was measured using the following method. 13 C-NMR analysis was performed. 13C-NMR analysis showed that the percentage of each carbon atom was 16.6% hydroxyl-bonded carbon (C-OH), 0.5% carboxyl carbon (C(=O)O), 0.4% carbonyl carbon (C=O), 14.7% hydrogen-bonded carbon, and 14.7% sp 3 Carbon was 67.8%.
[0063] <solid 13 C-NMR analysis〉 solid 13 The C-NMR analysis was performed by solid-state NMR using a solid-state NMR device (trade name "CMX-300 Infinity", manufactured by Chemagnetics). The measurement method and other conditions for the measurement are as follows: Measurement method: DD / MAS method Measurement nuclear frequency: 75.188829 MHz ( 13 C nucleus) Spectral width: 30.003 kHz Pulse width: 4.2 μsec (90° pulse) Pulse repetition time: ACQTM 68.26 msec, PD 15 sec Observation points: 2048 (data points: 8192) Reference material: polydimethylsiloxane (external reference: 1.56 ppm) Temperature: room temperature (approx. 22°C) Sample rotation speed: 8.0 kHz
[0064] Next, in the following examples, the nanodiamond obtained above was subjected to ring-opening addition polymerization with glycidol to produce a surface-modified nanodiamond modified with a group containing a polyglycerin chain on the surface. The surface-modified nanodiamond obtained in the examples was evaluated in terms of the following items.
[0065] <Solid content concentration> The solid content concentration of the surface-modified nanodiamond dispersion obtained as described above was measured as follows: A Teflon sheet was placed on a beaker, and several grams of the dispersion (sample) obtained above was placed on top of it, treated in a sand bath at 250°C for several hours, and after drying to a certain extent, vacuum dried at 70°C overnight, and the solid content concentration was calculated from the weight of the remaining solid content.
[0066] <Particle size measurement> The particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained as described above was measured by dynamic light scattering. Specifically, the particle size distribution of the surface-modified nanodiamonds was measured by dynamic light scattering (non-contact backscattering method) using a device manufactured by Microtrack Bell (product name "Nanotrac Wave II").
[0067] <Modification rate of modifying group> The ratio of modifying groups to nanodiamonds (ND) (modifying group weight / ND weight) was determined using TG / DTA (quartz pan, 30-800°C, heating rate 20°C / min) for the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained as described above (the solid obtained by drying the dispersion).
[0068] <Sodium nitrate aqueous solution mixing test> A 20-fold amount of 0.5M-NaNO3 aqueous solution was added to the surface-modified nanodiamond dispersion obtained as described above, and the presence or absence of turbidity or precipitation was observed.
[0069] <GPC Measurement> The surface-modified nanodiamond dispersion obtained as described above was subjected to GPC measurement under the following conditions. Analysis equipment: SHIMADZU, 10A Column: Shodex SB-806 x 2 + 802.5 with guard Column temperature: 40℃ Eluent: 0.5M-NaNO3 aqueous solution Flow rate: 0.6mL / min Detection: Shodex RI-101 (40℃) Porlarity (+), or UV254 Injection volume: 50μL Sample concentration: 0.5% (n=2 prepared, n=1 measured) (The obtained 1% aqueous solution was mixed with an equal amount of Milli-Q water to prepare a 0.5% aqueous solution, which was then filtered through a 0.45 μm filter to prepare the evaluation sample.) Standard sample: Easi Vial PEG / PEO
[0070] Example 1 Under a nitrogen atmosphere, 13.5 g of n-propanol and 0.1 g of the nanodiamond powder obtained in Production Example 1 were mixed to obtain a dispersion liquid, which was heated to 70°C. While maintaining the temperature at 70°C, 13.5 g of glycidol was dropped into this dispersion liquid over 1 hour, and after the dropwise addition, the dispersion liquid was aged at the same temperature for 10 hours. After the aging, the dispersion liquid was cooled to room temperature, and the reaction mixture was stopped by adding the same amount of water as the reaction mixture liquid. Then, the reaction mixture liquid was purified using a UF membrane (manufactured by Millipore, trade name "Amicon Bioseparations", made of polyethersulfone, molecular weight cutoff 30000). Permeation (solid-liquid separation using a membrane)-dilution [adding water to the remaining upper layer (valuable material)] was repeated, and purification was terminated when the total dilution ratio reached 1 million times. In this way, a dispersion liquid of surface-modified nanodiamond whose surface was modified by a group containing a polyglycerin chain was obtained. The particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 31 nm, D50 (median diameter) was 52 nm, and D90 was 169 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured and found to be 1.8. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0071] Example 2 The same procedure as in Example 1 was carried out except that the maturation time was changed to 4 hours, to obtain a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 2.02% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 28 nm, D50 (median diameter) was 49 nm, and D90 was 188 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 1.0. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and only slight turbidity and precipitation were observed.
[0072] Example 3 The same procedure as in Example 1 was carried out except that the maturation time was changed to 6 hours, to obtain a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 2.46% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 25 nm, D50 (median diameter) was 43 nm, and D90 was 83 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 1.3. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0073] Example 4 The same procedure as in Example 1 was carried out except that the same amount of ethylene glycol was used instead of n-propanol, to obtain a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The particle size distribution of the surface-modified nanodiamonds obtained above was measured by dynamic light scattering, and the particle size D10 was 23 nm, D50 (median diameter) was 40 nm, and D90 was 78 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured and found to be 0.7. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0074] Example 5 The same procedure as in Example 4 was carried out except that the reaction temperature was 150°C and the maturation time was 1 hour, to obtain a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 2.68% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 21 nm, D50 (median diameter) was 36 nm, and D90 was 78 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 0.5. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0075] Example 6 The same procedure as in Example 4 was performed except that the reaction temperature was 100°C, the maturation time was 4 hours, and the amount of glycidol used was 6.75 g, to obtain a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 1.75% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 22 nm, D50 (median diameter) was 37 nm, and D90 was 67 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 0.7. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0076] Example 7 The same procedure as in Example 4 was performed except that the reaction temperature was 100°C, the maturation time was 4 hours, and the amount of nanodiamond powder used as raw material was 0.5 g, thereby obtaining a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 1.97% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 21 nm, D50 (median diameter) was 38 nm, and D90 was 68 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 0.9. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0077] Example 8 The same operations as in Example 4 were performed except that the reaction temperature was 100°C, the maturation time was 4 hours, the amount of nanodiamond powder used as raw material was 2.2 g, the amount of ethylene glycol was 59.6 g, the amount of glycidol was 59.6 g, and the maturation time was 5 hours, to obtain a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 1.94% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 22 nm, D50 (median diameter) was 37 nm, and D90 was 69 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 0.9. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0078] Example 9 The same procedure as in Example 1 was carried out, except that the nanodiamond powder obtained in Production Example 2 was used instead of the nanodiamond powder obtained in Production Example 1, to obtain a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 4.21% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured by dynamic light scattering, and the particle size D10 was 3.9 nm, D50 (median diameter) was 5.0 nm, and D90 was 8.5 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 2.3. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0079] Comparative Example 1 The same procedure as in Example 1 was carried out except that the same amount of pyridine was used instead of n-propanol, and a pitch black slurry solution was obtained. A test was carried out on the obtained dispersion by mixing it with an aqueous sodium nitrate solution, and a precipitate was generated. It is assumed that the nanodiamond surface was not modified with polyglycerin.
[0080] Comparative Example 2 When N,N-dimethylformamide and glycidol were mixed, the mixture turned yellow, so experiments with nanodiamonds were not performed.
[0081] Comparative Example 3 When dimethyl sulfoxide and glycidol were mixed, the mixture turned yellow, so experiments with nanodiamonds were not performed.
[0082] Reference Example 1 (known formulation) According to the method of Production Example 1 of Patent Document 5, a dispersion of surface-modified nanodiamonds whose surfaces were modified with groups containing polyglycerin chains was obtained. The solid concentration of the surface-modified nanodiamond dispersion obtained above was measured to be 2.22% by weight. In addition, the particle size distribution of the surface-modified nanodiamonds obtained above was measured by dynamic light scattering, and the particle size D10 was 20.0 nm, D50 (median diameter) was 34.5 nm, and D90 was 66.3 nm. The modification rate of the modification group of the surface-modified nanodiamonds in the surface-modified nanodiamond dispersion obtained above was measured to be 1.1. In addition, a sodium nitrate aqueous solution mixing test was performed on the surface-modified nanodiamond dispersion obtained above, and no turbidity or precipitation was observed.
[0083] Variations of the invention according to the present disclosure are described below. [Appendix 1] In an aliphatic alcohol solvent having 2 to 4 carbon atoms, a nanodiamond or a surface thereof is represented by the following formula (1): -X 1 -H (1) [where, X 1 represents -NH-, -O-, -COO-, -PH(=O)O-, -S-, -SO3-, -SO2- or -SiO-. The surface-modified nanodiamond is modified with a group represented by the following formula (2) by ring-opening addition polymerization of glycidol. -XR (2) [In the formula, X represents a single bond, -NH-, -O-, -COO-, -PH(=O)O-, -S-, -SO3-, -SO2- or -SiO-, and R represents a polyglyceryl group.] The method for producing a surface-modified nanodiamond is characterized in that the surface-modified nanodiamond is modified with a group containing a polyglycerin chain represented by the formula: [Appendix 2] The nanodiamond may be produced by any method, such as detonation method, high temperature and high pressure method, static high pressure method, flux method, etc., and is preferably derived from diamond produced by detonation method (particularly, oxygen-deficient detonation method), and is particularly preferably derived from diamond synthesized by air-cooled detonation method. A method for producing a surface-modified nanodiamond described in Appendix 1. [Appendix 3] A method for producing a surface-modified nanodiamond according to appendix 1 or 2, wherein the nanodiamond (ND) has a particle size D50 (median diameter) of 3 to 200 nm, preferably 7 to 100 nm, and more preferably 10 to 40 nm. [Appendix 4] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 3, in which the particle size D50 (median diameter) of the nanodiamond (ND) or hydrogenated nanodiamond (ND-H) used as a raw material for producing the surface-modified nanodiamond is 3 to 200 nm, preferably 7 to 100 nm, and more preferably 10 to 40 nm. [Appendix 5] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 4, in which glycidol is successively added to a mixture of the aliphatic alcohol solvent having 2 to 4 carbon atoms and the nanodiamond or surface-modified nanodiamond used as a raw material under heating to carry out the reaction. [Appendix 6] A method for producing a surface-modified nanodiamond according to any one of Appendices 1 to 5, wherein the aliphatic alcohol having 2 to 4 carbon atoms is an aliphatic polyhydric alcohol, and preferably an aliphatic alcohol having 2 to 3 carbon atoms. [Appendix 7] The method for producing surface-modified nanodiamonds described in Appendix 6 is preferably used, wherein the aliphatic alcohol having 2 to 4 carbon atoms is an aliphatic monohydric alcohol such as ethanol, propanol, isopropyl alcohol, n-butanol, isobutyl alcohol, sec-butyl alcohol, or tert-butyl alcohol; or ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, or glycerin. [Appendix 8] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 7, wherein the nanodiamond or surface-modified nanodiamond used as a raw material is a solid (powder, etc.) obtained by drying a nanodiamond dispersion liquid with a positive zeta potential (preferably a nanodiamond dispersion liquid with a positive zeta potential of single digit), or a solid (powder, etc.) obtained by drying a nanodiamond dispersion liquid with a negative zeta potential (preferably a nanodiamond dispersion liquid with a negative zeta potential of single digit). [Appendix 9] A method for producing surface-modified nanodiamonds, as described in Appendix 8, in which the zeta potential of the nanodiamond dispersion having a positive zeta potential (i.e., a positive value for the zeta potential) is preferably 30 mV or more, more preferably 35 mV or more, and even more preferably 40 mV or more. [Appendix 10] A method for producing surface-modified nanodiamonds as described in Appendix 8, wherein the zeta potential of the nanodiamond dispersion having a negative zeta potential (i.e., a negative value of the zeta potential) is preferably -30 mV or less, more preferably -35 mV or less, and even more preferably -40 mV or less. [Appendix 11] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 10, wherein the amount of the aliphatic alcohol solvent having 2 to 4 carbon atoms used is preferably 10 to 2000 parts by weight, more preferably 15 to 300 parts by weight, and even more preferably 20 to 200 parts by weight, per 1 part by weight of the nanodiamond or surface-modified nanodiamond used as a raw material. [Appendix 12] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 11, wherein the amount of glycidol used is preferably 10 to 2000 parts by weight, more preferably 15 to 300 parts by weight, and even more preferably 20 to 200 parts by weight, per 1 part by weight of the nanodiamond or surface-modified nanodiamond used as a raw material. [Appendix 13] The method for producing a surface-modified nanodiamond described in any one of Appendices 5 to 12, wherein the heating temperature at which the glycidol is successively added and the reaction is carried out is preferably 40 to 180°C, more preferably 60 to 150°C, and even more preferably 80 to 125°C. [Appendix 14] The method for producing a surface-modified nanodiamond according to any one of Appendices 5 to 13, wherein the reaction of successively adding glycidol is preferably carried out under an inert gas atmosphere. [Appendix 15] The method for producing a surface-modified nanodiamond described in any one of Appendices 5 to 14, wherein the reaction of gradually adding glycidol may further comprise the use of a catalyst, which may be added in advance to a mixture of the aliphatic alcohol solvent having 2 to 4 carbon atoms and the raw material nanodiamond or the surface-modified nanodiamond, or may be added gradually to the mixture during the gradually adding of the glycidol. [Appendix 16] The catalyst may be either an acidic catalyst or a basic catalyst, and as an acidic catalyst, trifluoroboron etherate, acetic acid, or phosphoric acid is preferred, and as a basic catalyst, triethylamine, pyridine, dimethylaminopyridine, or triphenylphosphine is preferred. This is a method for producing a surface-modified nanodiamond described in any one of Appendices 5 to 15. [Appendix 17] A method for producing a surface-modified nanodiamond described in any one of Appendices 5 to 16, wherein the time for gradually adding the glycidol is preferably 10 minutes to 24 hours, more preferably 20 minutes to 2 hours. [Appendix 18] A method for producing a surface-modified nanodiamond described in any one of Appendices 5 to 17, wherein the maturation time after completion of the successive addition of glycidol is preferably 10 minutes to 24 hours, more preferably 20 minutes to 6 hours. [Appendix 19] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 18, wherein the ratio of surface modifying groups to nanodiamond (ND) (modifying group weight / ND weight) (=modification rate) obtained by TG / DTA measurement of the surface-modified nanodiamond is preferably 0.2 to 3.0, more preferably 0.4 to 2.4, and even more preferably 0.6 to 1.8. [Appendix 20] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 19, wherein the particle size D50 (median diameter) of the surface-modified nanodiamond obtained by DLS (dynamic light scattering) is preferably 20 to 60 nm, more preferably 30 to 50 nm. [Appendix 21] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 20, wherein the surface-modified nanodiamond does not cause precipitation or turbidity when mixed with an aqueous sodium nitrate solution. [Appendix 22] A method for producing a surface-modified nanodiamond described in any one of Appendices 1 to 21, wherein in GPC measurement, the main component peak has a position (retention time) and shape that is approximately the same as that of a known formulation (Production Example 1 in Patent Document 5), and no other by-products (impurities) are detected.
Claims
1. A nanodiamond or a surface thereof, which is represented by the following formula (1): -X 1 -H (1) [In the formula, X 1 is -NH-, -O-, -COO-, -PH(=O)O-, -S-, -SO 3 -, -SO 2 - or -SiO-. The surface-modified nanodiamond modified with a group represented by the formula (2) is subjected to ring-opening addition polymerization at 40 to 180° C. with 10 to 2000 parts by weight of glycidol per 1 part by weight of the nanodiamond or the surface-modified nanodiamond used as a raw material in an aliphatic alcohol solvent having 2 to 4 carbon atoms per 1 part by weight of the nanodiamond or the surface-modified nanodiamond used as a raw material, to form a surface-modified nanodiamond having a group represented by the formula (2) -X-R (2) [In the formula, X represents a single bond, -NH-, -O-, -COO-, -PH(=O)O-, -S-, or -SO 3 -, -SO 2 - or -SiO-, and R represents a polyglyceryl group. The method for producing a surface-modified nanodiamond is characterized in that the surface-modified nanodiamond is modified with a group containing a polyglycerin chain represented by the formula:
2. A method for producing surface-modified nanodiamonds as described in claim 1, in which glycidol is successively added to a mixture of the aliphatic alcohol solvent having 2 to 4 carbon atoms and the nanodiamond or surface-modified nanodiamond used as a raw material under heating to carry out the reaction.
3. 3. A method for producing surface-modified nanodiamonds according to claim 1 or 2, wherein the nanodiamonds or surface-modified nanodiamonds used as raw materials are powders obtained by drying a dispersion of zeta positive single digit nanodiamonds.
Citation Information
Patent Citations
Seed diamond ponder excellent in adhesion to artificial diamond film forming face
JP1999343197A
Functionalized diamonds, methods of making same, composite abrasives and abrasive tools containing functionalized diamonds
JP2003527285A
Nanodiamond
JP2007238411A
Dispersion method for nano-diamond
JP2008150250A
Nanodiamond and its producing method
JP2008303104A